Dr Francia - Middleton, A (Hodder & Stoughton, 2024)
José Gaspar Rodríguez de Francia has always divided opinion. For some of his subjects he was a paternal patriot, while for others he was a cruel, bigoted tyrant. His European and North American contemporaries clashed bitterly over whether he was a political Robin Hood, or an earthly Mephistopheles. Historians writing more recently have been similarly split about whether Francia was a devoted father to an emergent Paraguayan nation, or a man corrupted and even driven mad by the long-continued possession of absolute power.